Successful Recitations - Miles, Alfred H. (Alfred Henry), 1848-1929 (Salt Lake City, UT : Project Gutenberg, 2005)
"Successful Recitations" by Alfred H. Miles is a compilation of poetry designed for performance, likely curated in the early 20th century. This collection emphasizes the art of recitation, highlighting the importance of clarity, style, and emotional connection when presenting poetry in front of an audience. The book features a variety of recitatives from different authors, focusing on themes of patriotism, personal experience, and national pride. The opening of the work sets the stage for its purpose, discussing what constitutes a successful recitation, including the significance of picturesque and dramatic elements. Miles posits that the reader$1 (Bs ability to connect and command attention is crucial for effective recitation. He acknowledges that while the reader is central to the recitation's success, engaging content$1 (Boften selected by public preference$1 (Bplays a fundamental role. The initial sections feature foundational thoughts that guide the selection of pieces within the collection, aiming to inspire performers to deliver meaningful and memorable recitations. (This is an automatically generated summary.)s
Release date is 2005-12-22
E-text prepared by Roy Brown
Keywords: Recitations